2022
DOI: 10.3389/fitd.2022.985890
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of severe malaria and its clinical features in Gabonese children

Abstract: BackgroundMalaria remains one of the deadliest diseases in the tropic. Its severe form represents a major public health concern in sub-Saharan Africa. The study aimed to describe and analyze clinical features and outcomes of severe malaria in children from Libreville.MethodsMedical records (March 2018- to December 2019) from the emergency ward of the “Mother and Child University Hospital” were analyzed. Children hospitalized for malaria who met one or more criteria of the severe form rating according to the WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Hepatosplenomegaly was the frequent clinical finding in severe malaria and indicated a bad prognosis. 72,73 Smaller spleen indices were observed in CDDP and the mixture groups, indicating that platinum drugs could lessen splenomegaly. 10f, CDDP, and the mixture all obviously lessened the hepatomegaly.…”
Section: 13mentioning
confidence: 99%
“…Hepatosplenomegaly was the frequent clinical finding in severe malaria and indicated a bad prognosis. 72,73 Smaller spleen indices were observed in CDDP and the mixture groups, indicating that platinum drugs could lessen splenomegaly. 10f, CDDP, and the mixture all obviously lessened the hepatomegaly.…”
Section: 13mentioning
confidence: 99%
“…In Gabon, the main signs of severe malaria in children are severe anemia, neurological complications, hypoglycemia and respiratory distress. In children under 5 years of age, severe anemia is the most frequent clinical sign in severe forms [12,[14][15][16]. Previous studies have also reported that older children (and even adults) who would normally have acquired immunity may develop severe forms of the disease [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…These findings were within the leading clinical manifestations of severe malaria documented within and outside Nigeria. 20,24 In addition, cerebral malaria in the presence of acute kidney injury has the highest case fatality rate of 57%. Part of the pathogenic mechanisms during cerebral malaria include increased cytokines release, brain edema, and damage with an increased risk of death.…”
Section: Discussionmentioning
confidence: 99%